Campaign talk : why elections are good for us - Hart, Roderick P. (Book collections on Project MUSE., 2000)
"In the midst of today's increased media hype surrounding elections, Americans and the candidates they elect do seem to be listening to each other--as much as they did in years gone by. Hart's wide-ranging, objective investigation upends many of our stereotypes about political life and presents a new, more bracing, understanding of contemporary electoral behavior. Book jacket."--Jacket.